Peran Tim Pengawas Aliran Kepercayaan dan Penodaan Agama Pakem Menjaga Stabilitas Keamanan dan Kerukunan - Budiantoro, Totok; Hardyansah, Rommy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The role of the Supervision Team for Beliefs and Religious Sects (PAKEM) towards belief organizations in order to make efforts to overcome them by carrying out activities such as coordination meetings, conducting supervision and conducting dialogue with belief organizations, legal information and cooperation with agencies or government officials included in PAKEM and repressive efforts such as criminalization if indications of abuse and blasphemy are found. Obstacles for the Supervision Team for Beliefs and Religious Sects in supervising religious organizations. The absence of PAKEM standard operating procedures regarding specific rules regarding the implementation of PAKEM in the field. Limited facilities and infrastructure, lack of socialization regarding the existence of the PAKEM team. Optimizing the role of the Supervision Team for Beliefs and Religious Sects (PAKEM) towards belief organizations so that PAKEM standard operating procedures are immediately designed, so that there is procurement of facilities and infrastructure, so that socialization (counseling) is held routinely and comprehensively in the province from the district/city level regarding the existence and existence of the PAKEM team.